New voltemmetric sencor with phthalocyanine Co for the B6 vitamin determination in food additives; 2nd International Symposium on Recent Advances in Food Analysis (RAFA 2005) - Korotkova E. I. Elena Ivanovna (2005, 2005)
В фонде НТБ ТПУ отсутствует